Uganda Economic Update, 12th Edition, November 2018 : Developing the Agri-Food System for Inclusive Economic Growth - World Bank Group (World Bank, Washington, DC, 2018)
Real GDP growth rebounded strongly to 6.1 percent in FY17/18, from 3.9 percent the previous year. The rebound was largely driven by a pick-up in investments and exports, and on the back of strengthened credit to the private sector and good weather. Consequently, services, particularly information and communications, sustained strong growth, and food crop production recovered. Inper capita terms, however, this rebound translates into a 3.1 percent growth rate, because of the rapidly growing population. Moreover, the heavy reliance on rain-fed and subsistence agriculture drives the volatility in economic growth at the margin, with spillover effects on exportearnings, and a considerable impact on the poor’s income. Despite the rebound in economic growth in FY17/18, fiscal revenues stagnated, while the expenditure mix deteriorated further, with excessive current spending and under-execution in capital spending. Current spending exceeded last year’s outcome by a striking 1.4 percent of GDP and was above the budgeted amount by 32 percent. At the same time, the larger current spending was not used to finance investments in human capital.Therefore, one of the government’s priorities should be to rein in current spending and thereby keep public debt under control. Meanwhile, capital spending was 0.6 percent of GDP lower compared to the year before and fell short of the budgeted amount by 60 percent. Compared to peers, capital spending in Uganda stood at 4.4 percent of GDP in FY17/18, which is less than half the size ofRwanda’s capital outlays at 10.3 percent of GDP, and only 60 percent of Kenya’s at 7 percent of GDP. Combined with deficiencies in the ‘quality at entry’ of projects, cost escalations, and poor quality of some completed projects, this under-spending is constraining Uganda’s ambitions for rapid growth and socio-economic transformation. Therefore, concerted efforts are required to improve public investment management.